Schwannoma of the medial plantar nerve: a case report - Machado Filho, Adriano; Martins, Jefferson Soares; Pereira, Paulo Victor de Souza; Moura Júnior, Ademir Freire de (Journal of the Foot & Ankle, 2021)
We report the case of a 60-year-old woman with a schwannoma of the medial plantar nerve. She presented with the complaint of pain for about 2 years and a painful lesion in the medial plantar region of the left forefoot and on the second toe. Physical examination showed well-defined, firm tumor masses painful to palpation on the medial and plantar surface of the left forefoot and second toe. We surgically explored the area and excised 3 lesions, resulting in complete pain relief and no aesthetic complaints. Schwannomas of the medial plantar nerve are rare tumors, with only a few reports of cases extending to the forefoot. The finding of multiple schwannomas may be a red flag for the possible existence of local, painful, nerve lesions despite a negative Tinel sign. Appropriate surgical planning contributed to our successful intervention, without aesthetic, painful, or functional sequelae for the patient. Level of Evidence V; Therapeutic Studies; Expert Opinion.